RETRACTED: ASSESSMENT OF THE ADULT'S PERSONAL DEVELOPMENT AS AN INDICATOR OF THE QUALITY OF FURTHER EDUCATION - Natalia A. Biryukova (Russian State Vocational Pedagogical University, 2016)
RETRACTED ARTICLEThe aim of the presented publication consists in revision of approaches to additional education of adults in general; and particularly - in improvement of foreign language training process in the sphere of continuous training.The necessity of active foreign language skills by each modern person is caused by development of international cooperation in the most different spheres of activity. With respect thereto the organization of monitoring of quality of programs of additional education of adults acquires special relevance. However, the assessment of this quality is significantly complicated by lack of single standards and well-defined evaluation criteria.Methods. The classical and modern works devoted to the general questions of an assessment of quality of education and additional education of adults have been analysed during the research. D. Matyushkina's model for an assessment of quality of additional education, Yu. M. Orlov's technique «The requirement for achievement» and V. F. Ryakhovsky's test for determination of the general level of sociability are used as diagnostic tools.Results and scientific novelty. The author of the article suggests to consider the level of the trainee's personal development as the basic criterion for evaluation of productivity of education of adults. The main difficulties connected with studying by adults of a foreign language are analysed; the results of diagnostics of personal adult development mastering additional educational program «English without barriers» developed at the Mari state university are provided. The found positive dynamics following the results of monitoring on every personal (motivational, cognitive, communicative) program quality criterion proves its solvency and efficiency: the trainees' level of language knowledge and abilities, motivation of achievement of success have considerably increased; positive communicative installations are created; the incentives for further self-development have emerged.Practical significance. It is possible to develop further system of the concrete indicators allowing to build individual trajectories of training in the different directions of preparation in the system of further education on the basis of the output criteria for evaluation of educational activity of adults.